2015
DOI: 10.1515/cdbme-2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of local alterations in femoral bone mineral density measured via quantitative CT

Abstract: The aim of this study was to investigate the accuracy of bone mineral density (BMD) determined by quantitative computed tomography (qCT) based on in situ and ex situ scans of cadavers of variable stature. The in uence of surrounding tissue on the quanti cation of CT images of ex situ scanned femora was investigated in air and in water and compared with the in situ scanned femora. The study showed that the surrounding tissue has an impact on the grey value-based representation of the scanned object as well as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This is especially challenging in clinical routine. The literature on the effect of CT imaging on the finite element accuracy in skeletal modelling is scarce, and conclusions are often based on small study populations and low statistical power [1,24]. Most studies investigate the effect of different scan parameters and their effect on HU and BMD.…”
Section: Further Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially challenging in clinical routine. The literature on the effect of CT imaging on the finite element accuracy in skeletal modelling is scarce, and conclusions are often based on small study populations and low statistical power [1,24]. Most studies investigate the effect of different scan parameters and their effect on HU and BMD.…”
Section: Further Considerationsmentioning
confidence: 99%
“…Sitzer et al [24] reported differences in femoral diaphysis BMD measurements via QCT imaging (n = 3) of up to 17.5% when scanned in air and water compared to in vivo. Similarly, Keyak and Falkinstein [25] compared the FE predicted fracture loads of human femora scanned in situ and in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation